Visually Plotting Importance and Satisfaction to Identify Extension Clients’ Needs - Anil Kumar Chaudhary; Laura A. Warner (EDIS, 2016)
This is the second document in the Importance-performance Analysis series, a series of three about using importance-performance analysis (IPA) to prioritize Extension resources. This 4-page article covers how to collect data and use them to generate visual plots. IPA data plots are attractive and easy-to-understand visual maps that display importance and satisfaction scores for certain attributes. Written by Anil Kumar Chaudhary and Laura A. Warner, and published by the Department of Agricultural Education and Communication, May 2016.